Hydrological Impacts of Irrigation Schemes and Dams Operation in the Upper Niger Basin and Inner Niger Delta. - Maiga, Fatoumata (Université d'Ottawa / University of Ottawa, 2019)
The Upper Niger Basins (UNB) and the Inner Niger Delta (IND) are integral parts of the Niger River Basin, which flows through 10 countries and constitutes the third longest river in Africa. Natural climate variability and human interventions are two major factors affecting the hydrological regime in the UNB and IND. This study focuses on the later factor, by assessing the hydrological impacts of key existing and planned manmade structures and irrigation schemes in the UNB: the Sélingué (existing dam in Mali), four variants of the Fomi/Moussako dam (planned in Guinea), and Office du Niger (irrigation scheme located in Mali). The Fomi /Moussako dam will be located in the headwaters of the UNB and therefore, is expected to alter the hydrological regime in large parts of the watershed. Expected impacts include a reduction of the flood peak which will adversely affect critical ecosystems in the IND, and higher flows directly downstream of the dams in the dry season to sustain irrigation. These higher flows will, however, be consumed by Office du Niger irrigation scheme, leading to possible severe water shortages downstream of the irrigation scheme and in the IND. This is likely to affect the Malian economy and the poorest parts of its population, as the IND is crucial for the socio-economic and ecological preservation and development of the population surrounding it. The hydrological impacts of the dams and the irrigation scheme were evaluated in this study by developing a model of the IND and UNB using SWAT (Soil and Water Assessment Tool). After the model was calibrated, the effects of the dams and the irrigation scheme on selected flow statistics (mean and standard deviation) were determined at fourteen hydrological stations. In general, the results have shown that (1) the Fomi/Moussako dam will noticeably reduce the downstream high flows, and reduce the average flow; (2) if the Fomi/Moussako dam was to be built, the alternatives with the least storage volume (Moussako 388.5') will have the least impacts on the downstream flows. To assist in related decision making for various users, a Decision Support System (DSS) was also developed. The goal of the DSS is to help users analyze the effects of dams and irrigation on the flow regime by performing a comparative analysis (presence and absence of dams and irrigation in the river). A number of potential adaptation measures were also proposed.
Keywords: Niger River Basin; Hydrological impacts; Irrigation scheme; Dams